A Content Analysis of Personal Safety Apps: Are They Keeping Us Safe or Making Us More Vulnerable?. (February 2020) - Maxwell, L.; Sanders, A.; Skues, J.; Wise, L.
Despite personal safety apps claiming to increase safety, few studies have examined the usefulness of such apps in reducing public stranger violence. A content analysis of personal safety apps available in the iTunes store and Google Play identified location-based services, personal alarms, crowd-sourced hot spot data, and geofencing as the most common features. The majority of apps offered interventions either at the time of the event or post-event, suggesting that they may reduce a user's fear of crime but have limited usefulness in reducing vulnerability to victimization. Implications for users, app designers, and key stakeholders are discussed.